Menyingkap Lakon Auditor Internal Pemerintah dalam Melakukan Deteksi dan Pencegahan Fraud di Perguruan Tinggi - Gita Arasy Harwida; Mohamad Djasuli; Sujatmiko Wibowo (Pusat P2M Politeknik Negeri Batam, 2018)
Internal control has an important role in accordance with the achievment of good governance, and last but not least for the higher education which internal control is conducted by Inspectorate General (Itjen) and internal audit unit (SPI) in each state own university and polytechnique all around Indonesia. This research uses descrptive qualitative approach with explanatory model in order to deliver the message and analys data from various sources. Since the higher education moved to a new Ministry, the Inspector General put a new paradigm and a brand new internal control mechanism wich involve the internal audit unit in each state own university and polytechnique all around Indonesia as the armth lenghth of their internal control policy, thus, the integrated internal control will be achieved. Role conflict may occur both for Itjen and SPI evnthough in the different context and level. The lack of enacted law regarding the SPI and their rule in detecting and preventing Fraud are triggering the role conflict for them. However, role conflict will not make itjen and SPI give up to their assignment. The model of sinergy is advised in this article and hopefully will give a good contribution for the future integrity working model of Itjen and SPI in the future.